Strategi Pemasaran Dalam Upaya Meningkatkan Loyalitas Anggota di Baitul Maal Wa Tamwil Insan Mulia Palembang - Muhammad Aprizal Tahir; Nurseri Hasnah Nasution; Manalullaili Manalullaili (ScidacPlus, 2023)
This study aims to analyze the marketing strategy used by BMT Insan Mulia Palembang in an effort to increase member loyalty as well as the supporting and inhibiting factors in implementing the BMT Insan Mulia Palembang marketing strategy to increase member loyalty. This research is a type of field research (field research), this research approach is a qualitative descriptive approach. Sources of data used are primary and secondary data, with data collection techniques of interviews, observation and documentation. In addition, this study also uses data analysis methods including data reduction, data presentation and drawing conclusions. The results of this study indicate that BMT Insan Mulia Palembang has implemented a marketing strategy in an effort to increase member loyalty. The marketing strategy implemented uses the 7P marketing mix which includes product, price, place, promotion, people, physical evidence, and process. The result achieved from implementing the marketing strategy is that the number of loyal members has increased every year because BMT Insan Mulia always prioritizes the needs and desires of its members by providing maximum service and building positive relationships with members. then the supporting factors for BMT Insan Mulia's marketing strategy to increase member loyalty are convenience for members in making deposits and withdrawals, closeness between employees and members so that positive relationships are established, provision of quality facilities to support operational activities, and the provision of regular training to improve the quality of qualified human resources. is at BMT Insan Mulia Palembang so as to be able to create reliable and professional employees. The inhibiting factors are that there is still a minimum number of competent human resources in the field of marketers, there are still people who lack trust in institutions and there are many competitors so that members have more choices.